Adequacy of nutritional intake with caloric goal in a reference pediatric intensive care unit - Cieza-Yamunaqué, Liliana (2022)
Objetive. Nutritional intake in a reference pediatric intensive care unit is described and factors associated with inadequate achievement of the caloric goal are identified. Methods. Retrospective study that reviews the medical records of children under 14 years of age to identify clinical data, anthropometric nutritional assessment and energy expenditure according to the Schofield equation. Results. 65 patients were included, 54% male, age range from one month to 13 years, 60% admitted to the emergency department, most frequent diagnoses were shock and respiratory failure and and 49.2% presented normal nutritional status. In 28% of patients an adequate caloric goal was reached, 34% was excessive and 38% deficient. Nutritional support was started in the first 72 hours in 95% of patients, 84.6% by enteral route, 80% had nutrition interruptions. The inadequate achievement of the goal was more frequent in children under one year of age (51%, p=0.013) and in those who received enteral nutrition (93%, p=0.019).